HUBUNGAN HUKUM INTERNASIONAL DENGAN HUKUM NASIONAL - Tenripadang, Andi (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2016)
This paper examines the relationship between international law with national law. International law is a set of laws that mostly consists of principles and rules of behavior that bind states and therefore usually observed in the relations of countries to each other. In this study concluded that the primacy of the law regulating legal relations between states in international relations, recognized the two views, namely: (1) dualism, which is based on the theory that the connective power of international law rooted in the willingness of the country, international law and national law are two legal systems or devices are separated from each other (2) monism is founded on the idea of unity of the entire law governing human life. In the framework of this thinking, international law and national law are the two pieces instead of one larger entity that is the law that governs human life.